Systematic Review of University Reputation: Recent Trend and Future Research Agenda - Ali Mujahidin; Ahmad Saifurriza Effasa; Ahmad Faiz Khudlori; Budi Irawanto (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The main purpose of this study is to conduct a comprehensive review of previous research on university reputation, which currently lacks coherence. The study aims to address the gaps in the existing literature by providing a systematic discussion of the contributions made and highlighting the main issues found in previous research regarding the various aspects that influence university reputation, as well as its causes and effects. The approach used in this paper involves tracking all studies related to university reputation published between 2012 and 2021. After examining sources such as Scopus, Science Direct, and Web of Science, a total of 47 studies out of 295 were included in the analysis. The findings of this study demonstrate that university reputation is a multifaceted concept with diverse definitions and dimensions. The main purpose of this study is to conduct a comprehensive review of previous research on university reputation, which currently lacks coherence. The study aims to address the gaps in the existing literature by providing a systematic discussion of the contributions made and highlighting the main issues found in previous research regarding the various aspects that influence university reputation, as well as its causes and effects. The approach used in this paper involves tracking all studies related to university reputation published between 2012 and 2021. After examining sources such as Scopus, Science Direct, and Web of Science, a total of 48 studies out of 295 were included in the analysis. The findings of this study demonstrate that university reputation is a multifaceted concept with diverse definitions and dimensions. Additionally, the research confirms that several factors contribute to university reputation and that it has significant consequences. The study concludes by proposing recommendations for future research, including theories, methodologies, and potential areas of investigation. Furthermore, a comprehensive framework is presented as a result of this study